Analyzing North Macedonia’s Size and Power in the Context of its Foreign Policy Conduct - Gjeraqina Leka; Shefik Shehu; Ebrar Ibraimi (Academicus International Scientific Journal)

(untitled)
The purpose of this article is to explore the smallness and weakness of the Republic of North Macedonia by observing its foreign policy behavior since its independence to the present day. Instead of focusing on criteria that rely on internal determining factors, the aim of this paper is to investigate the size and power of a state by observing its external behavior. To fulfill this purpose, the article employs a case study methodology. Specifically, it uses the case of the Republic of North Macedonia to observe and evaluate its smallness and weakness based on the demonstrated foreign policy behavior of this state, especially in its efforts to deal with external challenges. The contextualized analysis is expected to contribute to an enhanced understanding of how the main patterns of a state’s foreign policy behavior may dictate its size and power and consequently its place and role within the international system.